Comparison of "Live High-Train Low" in normobaric versus hypobaric hypoxia - Saugy, J. J.; Schmitt, L.; Cejuela, R.; Faiss, R.; Hauser, A.; Wehrlin, J. P.; Rudaz, B.; Delessert, A.; Robinson, N.; Millet, G. P. (PLOS ONE, 2014)
We investigated the changes in both performance and selected physiological parameters following a Live High-Train Low (LHTL) altitude camp in either normobaric hypoxia (NH) or hypobaric hypoxia (HH) replicating current "real" practices of endurance athletes. Well-trained triathletes were split into two groups (NH, n = 14 and HH, n = 13) and completed an 18-d LHTL camp during which they trained at 1100-1200 m and resided at an altitude of 2250 m (PiO2 = 121.7+/-1.2 vs. 121.4+/-0.9 mmHg) under either NH (hypoxic chamber; FiO2 15.8+/-0.8%) or HH (real altitude; barometric pressure 580+/-23 mmHg) conditions. Oxygen saturations (SpO2) were recorded continuously daily overnight. PiO2 and training loads were matched daily. Before (Pre-) and 1 day after (Post-) LHTL, blood samples, VO2max, and total haemoglobin mass (Hbmass) were measured. A 3-km running test was performed near sea level twice before, and 1, 7, and 21 days following LHTL. During LHTL, hypoxic exposure was lower for the NH group than for the HH group (220 vs. 300 h; P<0.001). Night SpO2 was higher (92.1+/-0.3 vs. 90.9+/-0.3%, P<0.001), and breathing frequency was lower in the NH group compared with the HH group (13.9+/-2.1 vs. 15.5+/-1.5 breath.min-1, P<0.05). Immediately following LHTL, similar increases in VO2max (6.1+/-6.8 vs. 5.2+/-4.8%) and Hbmass (2.6+/-1.9 vs. 3.4+/-2.1%) were observed in NH and HH groups, respectively, while 3-km performance was not improved. However, 21 days following the LHTL intervention, 3-km run time was significantly faster in the HH (3.3+/-3.6%; P<0.05) versus the NH (1.2+/-2.9%; ns) group. In conclusion, the greater degree of race performance enhancement by day 21 after an 18-d LHTL camp in the HH group was likely induced by a larger hypoxic dose. However, one cannot rule out other factors including differences in sleeping desaturations and breathing patterns, thus suggesting higher hypoxic stimuli in the HH group.